Introduction - Costa, Cíntia (Guará Journal, 2025)
Created in 2014, the Maria Filina Award for Extension Merit was established by the Office of Extension (Proex) of the Federal University of Espírito Santo (Ufes) with the purpose of recognizing the work carried out by coordinators and teams of extension projects and programs developed at Ufes, giving visibility to these extension activities, encouraging undergraduate student participation, and promoting student leadership in extension practices. This year, a total of 40 people were involved in the Maria Filina Award, including members of the Organizing Committee, evaluators, scholarship holders, and other collaborators. However, the main protagonists of this great “celebration” are the teams behind the 131 participating projects and programs. From capoeira to breastfeeding, from elderly care to the creation of technological solutions to improve assistance for people with autism, from the teaching of Botany to the teaching of Python, the Award is a beautiful showcase that presents a sample of Ufes projects that have been benefiting the society of Espírito Santo.